Strategic Management in Investment Enhancement Governance in Central Mamuju Regency - Aslamsyah, Andi Muhammad; Ahmad, Badu; Ibrahim, Muhammad Akmal (KnE Social Sciences, 2025)
Regional investment is a key factor in efforts to improve regional development. This study aims to analyze strategic management in the governance of increasing investment in Central Mamuju Regency. The research method uses qualitative studies. Research informants comprise various stakeholders involved in investment management in Central Mamuju Regency. Data collection consists of observation, in-depth interviews, and document searches. Data sources include primary and secondary data. The study results show that local governments face various challenges, such as limited capacity and quantity of human resources, the absence of regional regulations related to investment, and suboptimal cross-sector coordination. Basic infrastructure such as roads, clean water, and telecommunication networks remain the obstacles affecting investment attractiveness. In addition, the lack of micro-investment data, the potential for agrarian conflicts, and the risk of natural disasters also hamper the investment climate. The implementation of the strategy has not been fully integrated with regional development policies. The minimal involvement of the private sector and the community, as well as the absence of comprehensive evaluation instruments, are challenges in ensuring the sustainability of investment strategies. Evaluation based on performance indicators such as the human capital index, SPBE, and regional competitiveness index are the first steps to improve investment governance in the future. This study recommends the importance of strengthening institutions, digitalizing services, and cross-sector collaboration in creating a sustainable investment climate in Central Mamuju.